500 Jahre Theologie in Hamburg: Hamburg als Zentrum christlicher Theologie und Kultur zwischen Tradition und Zukunft ; mit einem Verzeichnis sämtlicher Promotionen der Theologischen Fakultät Hamburg - Steiger, Johann Anselm (Arbeiten zur Kirchengeschichte, 2005)
This essay collection presents a multi-facetted overview of five centuries of cultural history and the history of Christianity in Hamburg; at the same time, it places local historical aspects in the wider context of overall developments in the history of ideas. Johann Anselm Steiger ist Professor für Kirchen- und Dogmengeschichte an der Universität Hamburg.